Mucocutaneous manifestations in dengue: A study among children at a tertiary care center in South India - Jogin Veeresh; Sambasiviah Chidambara Murthy; Banavasi Vishwanath (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dengue, a viral illness, is a major public health problem. Mucocutaneous manifestations are known to occur in this illness. Over the past three decades, there has been a dramatic global increase in the incidence of dengue fever (DF). Our objective was to study the frequency and pattern of mucocutaneous manifestations of DF in children. Methodology: A total of 210 consecutive cases, which were serologically confirmed and admitted to pediatric ward over a period of 12 months (January to December 2018), were included. A detailed clinical history, examination and relevant investigations were carried out. Data were entered into a pro forma and analyzed using simple statistical methods and Chi-square test (wherever applicable). Results: The most common age group affected was 4.1-8 years with a mean age of 6.3 ± 3.9 years. Male children were more commonly affected, with majority from urban areas. Maximum cases were noted during the months from October to December, i.e., winter season. Mucocutaneous findings were noted in 112 (53.3%) cases. Cutaneous rash was present in 43 (20.1%) cases. The most common site involved was trunk, followed by face and others. Macular erythema was the most common type of rash. Onset of rash was more commonly seen in children with depleted platelet count. Ocular and oral mucosae were involved in 56 (26.7%) and 42 (20.1%) cases, respectively. Conclusion: Mucocutaneous manifestations are relatively common in children with dengue. Cutaneous rash may be a useful clinical clue for early diagnosis of dengue. Awareness of mucocutaneous manifestations helps in early recognition and proper management of dengue.